Pengaruh Bacillus Thuringiensis terhadap penggerek batang jagung Ostrinia Furnacalis (Lep. Pyralidae) - Harnoto Harnoto (Perhimpunan Entomologi Indonesia, 2005)
The effect of Bacillus thuringiensis to the mortality of corn stemborer Ostrinia furnacalis (Lep. Pyralidae). The study was conducted at the laboratory of Bogor Research Institute for Agricultural Biotechnology and Genetic Resources during 2005. The objective of this study was to evaluate the effect of the dosages of Bacillus. thuringiensis var. aizawai and var. Kurstaki on the mortalities of larvae of corn stemborer Ostrinia furnacalis. Completely randomize design was used with seven treatments. Each treatment was repeated four time with ten larvae per replication. The treatments were three formulation dosages of B. thuringiensis var. aizawai, i.e. 0,5; 1,0; and 2,0 g/l, thee formulation dosages of B. thuringiensis var. Kurstaki, i.e. 0,5; 1,0; and 2,0 g/l, and untreated control. Second instar larvae of O. furnacalis was used in this study. B. thuringiensis was contaminated to the surface of artificial diet with a small paint brush. The result showed that B. thuringiensis var. kurstaki at the dose rate of 1,0 g/l was toxic to the test insect while B. thuringiensis var. aizawai at the dose rate of 2,0 g/l was toxic to the test insect B. thuringiensis var. kurstaki was more toxic than B. thuringiensis var. aizawai to the corn stemborer.